Phytochemicals, Two New Sulphur Glycosides and Two New Natural Products, from Shepherd’s Purse Seed and Their Activities - Wei, Zhen-Zhen; Ge, Chun-Bo; Wang, Yu-Jie; Li, Bin; Tian, Ying; Zhou, Ti-Qiang; Liu, Shu-Chen; Yi, Jian-Feng (Molecules (Basel, Switzerland), 2024)
Two new sulfur glycosides, bursapastoris A–B (3–4), were extracted and isolated from shepherd’s purse seed, along with two new natural products, 11-(methylsulfinyl)undecanoic acid (2) and 10-(methylsulfinyl)decanoic acid (1). Their structures were determined though infrared spectroscopy, one-dimensional nuclear magnetic resonance (1H and 13C), and electrospray ionization mass spectrometry. Additionally, the structures of 3–4 were further identified by two-dimensional nuclear magnetic resonance (HMBC, HSQC, 1H-1H COSY, and NOESY). Compounds 1–4 showed relatively favorable docking to NF-κB. Unfortunately, we only discovered that compound 1–4 had weak anti-radiation activity at present. Therefore, further research regarding the biological activity of these organosulfur compounds is required at a later stage.